Cx26 keratitis ichthyosis deafness syndrome mutations trigger alternative splicing of Cx26 to prevent expression and cause toxicity in vitro. Issue 8 (7th August 2019) - Cook, Jonathan; de Wolf, Elizabeth; Dale, Nicholas
Abstract : The Cx26 mRNA has not been reported to undergo alternative splicing. In expressing a series of human keratitis ichthyosis deafness (KID) syndrome mutations of Cx26 (A88V, N14K and A40V), we found the production of a truncated mRNA product. These mutations, although not creating a cryptic splice site, appeared to activate a pre-existing cryptic splice site. The alternative splicing of the mutant Cx26 mRNA could be prevented by mutating the predicted 3′, 5′ splice sites and the branch point. The presence of a C-terminal fluorescent protein tag (mCherry or Clover) was necessary for this alternative splicing to occur. Strangely, Cx26 A88V could cause the alternative splicing of co-expressed WT Cx26—suggesting a trans effect. The alternative splicing of Cx26 A88V caused cell death, and this could be prevented by the 3′, 5′ and branch point mutations. Expression of the KID syndrome mutants could be rescued by combining them with removal of the 5′ splice site. We used this strategy to enable expression of Cx26 A40V-5′ and demonstrate that this KID syndrome mutation removed CO2 sensitivity from the Cx26 hemichannel. This is the fourth KID syndrome mutation found to abolish the CO2 -sensitivity of the Cx26 hemichannel, and suggests that the altered CO2 -sensitivity could contribute to the pathology of this mutation. Future research on KID syndrome mutations should take care to avoid using a C-terminal tag to track cellular localization and expression or if this is unavoidable, combine this mutation with removal of the 5′ splice site.